2017
DOI: 10.1097/mao.0000000000001303
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study Evaluating the Impact of Otology Surgery Videos on Otolaryngology Resident Education

Abstract: The varied videos were rated highly in terms of usefulness, promoting self-efficacy and as a high-priority for a resident's surgical preparation. Multimedia-formatted training videos should be further explored for this generation of electronic-learners. Future studies with a larger cohort, objective approaches, and multidisciplinary involvement are needed to determine the full impact of this education medium on surgical-training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 14 publications
0
40
0
Order By: Relevance
“…), selected initial propositions based on personal experience, video guidelines of major journals, and a literature review. 3,5,10,[12][13][14][15][17][18][19][20][21][22][23] A Delphi questionnaire was created, and the propositions were reviewed online by the entire consensus committee in three rounds. Blinded feedback was shared among respondents between each round, and the respondents were able to suggest new propositions at the end of round 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…), selected initial propositions based on personal experience, video guidelines of major journals, and a literature review. 3,5,10,[12][13][14][15][17][18][19][20][21][22][23] A Delphi questionnaire was created, and the propositions were reviewed online by the entire consensus committee in three rounds. Blinded feedback was shared among respondents between each round, and the respondents were able to suggest new propositions at the end of round 1.…”
Section: Methodsmentioning
confidence: 99%
“…Educational videos have been shown to increase surgical skills and, as such, are increasingly included in the resident curriculum to expedite the training of young surgeons. [1][2][3][4][5][6][7][8][9][10] Many different video platforms exist, the most used being YouTube, but also specialized surgery-orientated platforms or online medical journal platforms. 4,[10][11][12] Educational surgery videos that are available online are too often of insufficient quality and are rarely peer reviewed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scoping review indicated that a large number of YouTube videos exist across a variety of medical topic areas, including: nephrology [36], geriatric care [16], anatomy [35], otology/neurotology [37], surgery [29], and heart failure [22]. Generally, only a small number of studies demonstrated the effectiveness of YouTube videos at higher evaluative outcome levels as an effective educational resource in medical education.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that involved an educational intervention which reported evaluative outcomes (n=6) explored the use of YouTube in providing educational content across a variety of subject areas, including: nephrology [36], geriatric care [16], anatomy [35], otology/neurotology [37], surgery [29], and heart failure [22]. summarizing the content of a recent guideline on the management of heart failure, in an effort to increase the dissemination of guidelines among physicians.…”
Section: Papers Identified Inmentioning
confidence: 99%